A laboratory study of the effects of porosity and bed tilting on the discharge rate of groundwater (2005)
The study of movement of underground water helps to predict the extent of flow in as much as we can determine the volume rate among other things. Sand samples from river bed were used as porous media, a laboratory experiment was set up to look at longitudinal dispersion in term of volume of liquid flowing across a unit cross sectional area per unit time in these materials. Water was made to flow through a cylindrical pipe drilled sideways at intervals. Values of pressure were taken at regular interval and using appropriate basic equations, the volume flux rate was determined at various angles of tilt, from which volume rate of flow was also determined. A graph of volume rate of flow against angle of tilt gives the value of volume rate of flow as 1.00 ' 10-10 m3/s irrespective of porosity and permeability of the medium provided that the angle of tilt is 1.42°